Sistema de gestión de la seguridad y salud en el trabajo basado en la norma ISO 45001:2018 para la Empresa Eléctrica Ambato. - Martínez Garcés, Luis Daniel (2026)
This research arose from the need to strengthen the Occupational Health and Safety Management System of the Ambato Electric Company by applying ISO 45001. The research employs a mixed methods approach to develop a proposal to reduce workplace risks and promote a culture of prevention and protection in occupational health and safety. The research begins with a compliance assessment using a checklist developed in accordance with ISO 45001:2018. This provides a starting point for developing the proposal, which involves improving and expanding upon the requirements through various procedures. To prioritize intervention, a risk assessment methodology was applied. The results indicate that the Distribution Process presents the highest risk levels due to its operational nature, including working at heights, direct exposure to electrical hazards, awkward postures, lifting heavy loads, physical overexertion, and mental strain. Consequently, a specific management manual was designed for this area, establishing preventive control parameters and the use of the IPERC matrix. With the development of this proposal, the company will have the foundations to apply for and certify to the international standard ISO 45001:2018, ensuring the physical and mental well being of workers and enabling its replication and progressive adaptation across all departments of the Ambato Electric Company.